Psycho-spiritual intervention to reduce anger level among delinquent teenager - Hamizah Muhammad; Nor Shakirah Mohd Sakari; Syed Hadzrullathfi Syed Omar (Intelektual Pustaka Media Utama, 2022)
To this day, delinquent among teenagers remain the most critical social issue facing the Malaysian nation. This study examined the effects of psycho-spiritual intervention in reducing the level of anger among delinquent teenagers from correctional and rehabilitation centers in Terengganu. This study employed quasi-experimental research with one group pretest-posttest. The 24 female delinquent teenagers from correctional and rehabilitation centers in Terengganu were involved in this study. Differences in anger levels were evaluated based on the pretest and posttest scores, using the clinical anger scales (CAS). Descriptive analysis and pair sample t-test were used to analyze data. Overall, the pre and post-test mean scores showed a decrease in delinquent teenager’s anger levels. Pair sample t-test showed a significant difference in anger level before and after the psycho-spiritual intervention. It is shown that psycho-spiritual intervention is effective to reduce the levels of anger among teenagers who are involved in delinquent behavior.